Investigating the Use of Basalt Rock Powder in the Partial Replacement of Cement in Plain Concrete - Kelly Wayomirwoth (Uganda Christian University, 2024)
This research study focused on investigating the optimum replacement of Basalt Rock powder (BRP) that can be used to partially replace cement as a cement supplementary material (SCM) while achieving the maximum suitable compressive strength. The Basalt rocks used in this study were collected and crushed from Mugarama site in Kibaale District to form powder. The physical and mechanical properties of concrete ingredient such as sand and coarse aggregates were determined and these included sieve analysis, ACV, AIV, moisture content, flakiness index, specific gravity and water absorption. The properties of the BRP were determined by carrying out different tests such as sieve analysis, x-ray fluorescence, water absorption with results provided in chapter 4 below. The control mix of a cement content 430Kg, fine aggregate, 675kg, water 206kg and coarse aggregate of 1007kg. The percentage replacement of cement with BRP varied from 0, 10,15,20,25 and 30%. Concrete cubes of sizes 150mmx150mmx150mm were casted and evaluated for 7 and 28 days. Increase in percentage replacement of cement with BRP showed an increase in compressive strength from 0% to 15% attaining the highest value of 43.9Mpa and then gradually decreased with increasing percentage replacement of BRP. The setting time decreases while workability increases, with an increase in BRP percentage replacement. The compressive strength, setting time and workability were all lying in the acceptable ranges according to literature, 43.9Mpa, 7.7hrs and 87mm respectively. The 15% is the optimum percentage replacement since its strength is well above the control concrete of 40.5Mpa, and target strength of 35.1Mpa.